2023
DOI: 10.1039/d3qi01425h
|View full text |Cite
|
Sign up to set email alerts
|

Low-coordination single Ni atoms on graphitic C3N4 for nitrite electroreduction to ammonia

Hongyan Zhao,
Jiaqi Xiang,
Guike Zhang
et al.

Abstract: Electrocatalytic converting NO2- to NH3 (NO2RR) offers an attractive approach to realize both hazardous NO2- abatement and sustainable NH3 production. Single-atom catalysts (SACs) show a great potential for N-cycle electrocatalysis,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…The synthesis of Co 1 /C 3 N 4 is achieved through an impregnation method (Figure 1a). 26 In the X-ray diffraction (XRD) pattern of Co 1 /C 3 N 4 (Figure S1), no distinct diffraction peaks corresponding to Co clusters/particles are observed, suggesting that Co species are highly dispersed on C 3 N 4 . Transmission electron microscopy (TEM) analysis shows that Co 1 /C 3 N 4 has a thin folded nanosheet structure (Figure S2a), and the high-resolution TEM (HRTEM) image shows that Co 1 /C 3 N 4 exists in an amorphous state (Figure S2b), similar to those of pristine C 3 N 4 (Figure S3), indicating that Co species are highly distributed on the C 3 N 4 support.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The synthesis of Co 1 /C 3 N 4 is achieved through an impregnation method (Figure 1a). 26 In the X-ray diffraction (XRD) pattern of Co 1 /C 3 N 4 (Figure S1), no distinct diffraction peaks corresponding to Co clusters/particles are observed, suggesting that Co species are highly dispersed on C 3 N 4 . Transmission electron microscopy (TEM) analysis shows that Co 1 /C 3 N 4 has a thin folded nanosheet structure (Figure S2a), and the high-resolution TEM (HRTEM) image shows that Co 1 /C 3 N 4 exists in an amorphous state (Figure S2b), similar to those of pristine C 3 N 4 (Figure S3), indicating that Co species are highly distributed on the C 3 N 4 support.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The synthesis of Co 1 /C 3 N 4 is achieved through an impregnation method (Figure a) . In the X-ray diffraction (XRD) pattern of Co 1 /C 3 N 4 (Figure S1), no distinct diffraction peaks corresponding to Co clusters/particles are observed, suggesting that Co species are highly dispersed on C 3 N 4 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Diverse precious metals and non-precious metal-based compounds have been experimentally and theoretically explored for NO 2 RR, and their performances have been further improved by several strategies. 17–23 For instance, amorphization has been reported to be an efficient approach for effectively engineering the electronic structures of materials to enhance their catalytic properties. 24–27 Previous reports have demonstrated that amorphization can create abundant structural defects and dangling bonds on the catalyst surface, which can serve as active sites to accelerate ammonia electrosynthesis with high selectivity and activity, 27–29 rendering amorphous materials fascinating catalysts for efficient NO 2 RR.…”
mentioning
confidence: 99%
“…S8 †), as NO 2 − adsorption is a critical step to trigger the NO 2 RR. 14,39,40 After the MD simulations, it is shown in Fig. 4a that the degree of NO 2 − accumulation on u-Cu is more obvious than that on Cu.…”
mentioning
confidence: 99%